The Emergence of Qnr-resistance Among Klebsiella pneumoniae spp in Zahedan: Qnr-resistance Among Klebsiella pneumoniae spp - Mohammadzadeh Rostami, Farzaneh; Shalibeik, Saman; Shahraki, Shahram (Iranian Journal of Pharmaceutical Sciences, 2018)
Although quinolone resistance results mostly from chromosomal mutations in Klebsiella pneumoniae, it may also be mediated by plasmid – encoded qnr determinants. Plasmid-mediated quinolone resistance (PMQR) was increasingly identified in Enterobacteriaceae family worldwide. The aim of this study was to investigate the prevalence of qnr genes in clinical isolates of Klebsiella pneumoniae spp in Zahedan, south-East of Iran. In this sectional-descriptive study which was performed in 2013, clinical isolates of k. pneumoniae (n=184) were collected from patients referred to 3hospitals of Zahedan. The presence of the qnr gene was screened by PCR using specific primers for qnrA, qnrB, qnrS and qnrC in extracted plasmid DNA. Of 184 K. pneumoniae clinical isolates, 45 isolates were positive for the qnr gene. The prevalence of qnrA, qnrB and qnrS clusters among these isolates were 8 (17.7%), 22 (48.8%), 4(8.88%) respectively and qnrC was not identified in any isolate. Another 6(13.33%) possessed both qnrA and qnrB genes and 5(11.11%) possessed both qnrB and qnrS. qnr are widely distributed worldwide. Community-acquired and nosocomial pathogens and the emergence of qnr-mediated quinolone resistance among clinical K.pneumoniae isolates are described for the first time in Iran.